Sustainable Tourism in the Social Media and Big Data Era - Nam, Yoonjae; Bae, So Young (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
• The aim of this Special Issue is to examine the current major topics concerning the use of social media and big data in sustainable tourism practices and to encourage interdisciplinary discussion among researchers regarding these issues. • This Special Issue covers all relevant areas of the debate, including 15 selected papers based on the following core ideas: smart tourism and big data, social media in the tourism industry, and online reviews and tourist behaviors. • This Special Issue discusses wide-ranging topics and research questions with regard to the smart tourism city, the impact of social media, online reviews, and tourist behaviors, and it represents a call to action for scholars to engage with broader social issues.